2005
DOI: 10.1088/0953-8984/17/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and structure formation in thin polymer melt films

Abstract: The stability of thin liquid coatings plays a fundamental role in everyday life. We studied the stability conditions of thin (3 to 300 nm) liquid polymer films on various substrates. The key role is played by the effective interface potential φ of the system air/film/substrate, which determines the dewetting scenario in case the film is not stable. We describe in this study how to distinguish a spinodal dewetting scenario from heterogeneous and homogeneous dewetting by analysing the emerging structures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
204
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(220 citation statements)
references
References 72 publications
14
204
1
1
Order By: Relevance
“…101 It is commonly admitted that nucleation occurs in the early stage of dewetting and spinodal dewetting is promoted for thin films. 101,102 On gold samples, the values of polar components (g + + g À ) were ten times lower than those of the apolar one (g LW ); hence, following Lee's idea, it indicated that gold surface exhibits a strong stabilizing force towards the film. The SEM images showed the beginning of the dewetting process through the heterogeneous nucleation (white spots) stopped before the growth of holes…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…101 It is commonly admitted that nucleation occurs in the early stage of dewetting and spinodal dewetting is promoted for thin films. 101,102 On gold samples, the values of polar components (g + + g À ) were ten times lower than those of the apolar one (g LW ); hence, following Lee's idea, it indicated that gold surface exhibits a strong stabilizing force towards the film. The SEM images showed the beginning of the dewetting process through the heterogeneous nucleation (white spots) stopped before the growth of holes…”
Section: Discussionmentioning
confidence: 99%
“…This was also confirmed by the random distribution of holes characteristic of heterogeneous nucleation according to Seeman. 101 This organization was stable because the gold surface was not sensitive to pH changes. On utilizing titanium dioxide, the contributions of polar and apolar components were rather comparable.…”
Section: Q8mentioning
confidence: 99%
“…These omnipresent interactions arise from polarization fluctuations in the materials and are well known to affect the stability of thin films 16,[19][20][21][22] . For two parallel layers, separated by a distance d, the interaction due to the dispersion forces is given by W = -A/(12πd 2 ), with A the effective Hamaker constant for the film sandwiched between a substrate and gas (usually air).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in case of thin films, the phenomenon of dewetting plays a major role in determining the morphology of the film. Dewetting [2,3] occurs depending on the balance between the thickness of the melt polymer or of the solution used for the film preparation, the liquid/vapor surface tension and the density of the liquid. Dewetting is much more probable for thin films than for bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…The dewetting processes in thin films are primarily of two kinds, the heterogeneous nucleation and the spinodal dewetting [2,3]. Both mechanisms lead to the creation of holes.…”
Section: Introductionmentioning
confidence: 99%